(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
This research attempts to account for new distinctions and relationships between such classic philosophical concepts as “being” (“being” and “being in time”), “consciousness”, “identity”, and “authenticity”, all of which are thought of from the fundamental concept of “being in time”. It aims to ensure the development of a stream of philosophical thought, whose object and horizon is America and The American, thought of from the point of view of a Latin American philosophy.